COMPARISON OF FUNGAL DIVERSITY OF LOCAL AND EXOTIC RICE (ORYZA SATIVA L.) GERMPLASM FOR THEIR SEED HEALTH - M. Ashfaq; M. S. Shaukat; M. Akhter; M. S. Haider; U. Mubashar; S. B. Hussain (Journal of Animal and Plant Sciences, 2015)
Rice is one of the major cereal crop of the world. Its production potential is lower than in Pakistan because of rice seed mycoflora. Present study provides analysis of fungal mycoflora from rice seeds of 39 different germplasm lines (08 local and 30 exotic). Fungi were isolated from rice by agar and blotter paper methods. Surface sterilization of rice samples were done by using ethanol and sodium hypochlorite (NaOCl) (2% each). Total of 18 different fungal species belong to 8 different genus were isolated from tested exotic and local germplasm lines of rice. The diversity of fungal species were observed included Alternaria juxtiseptata, five species of Aspergillus, Cladosporium cladosporoides, three species of Curvularia, two species of Drechslera biseptata, Fusarium globosum, Mucor sp., Penicillium oxalicum, Phoma sp., Rhizoctonia sp. and Rhizopus arrhizus. Curvularia lunata had highest percent frequency in all the local germplasm lines although Penicillium globosum, Rhizoctonia sp., Phoma sp. were isolated in higher frequency from blotter paper method as compared to agar plate. In the preview of such high association of mycoflora with stored rice grains, a proper seed treatment is the need of the hour. Moreover, it must be evaluated for all the cultivated as well as research germplasm for proper control of these seed mycoflora for future utilization/availability, production of healthy and high yielding rice varieties to the farmers community.
Keywords: Rice; mycoflora; agar plate method; blotter paper method; Curvularia lunata